The a/r/t that permeates a dissertation on democratic education (Revista Apotheke, 2024)
This text emphasizes the aesthetic and artistic elements explored in the development of a doctoral dissertation in Education by a professor of Visual Arts, whose theme was the relationship between art and democratic education within the scope of Federal Institutes of Education, Science and Technology – Federal Institutes in a reactionary context. It was desired, through a type of curation, the creation of a verbal-visual montage that expressed the a/r/t that permeated the process of research and elaboration of this thesis, enabling a reflection on processes of creation in the field of research in education. The material from which this curation was carried out is composed of: works and pictures from two editions of an art exhibition with original work, the first being held in 2018 and the second in 2023; photographic and video records of the creation of a defense-performance, as a format for public presentation of the developed dissertation; and a video performance developed from the public defense of the dissertation. These visual and audiovisual documents generated were selected and explored in this text to expose and express an a/r/t/graphic body that seeks to understand and experience the opportunities and challenges of being an artist-researcher-teacher and the relationship between art and democratic education as resistance to reactionary discourses in education.
Keywords: democratic education; a/r/tographer; art; reactionary speech